Genotypic spectrum underlying tetrahydrobiopterin metabolism defects: Experience in a single Mexican reference center - Vela-Amieva, M.; Alcántara-Ortigoza, M. A.; Ibarra-González, I.; González-del Angel, A.; Fernández-Hernández, L.; Guillén-López, S.; López-Mejía, L.; Carrillo-Nieto, R. I.; Fiesco-Roa, M. O.; Fernández-Lainez, C. (Frontiers in Genetics, 2022)
Background. Pterin profiles or molecular analyses of hyperphenylalaninemia (HPA) caused by phenylalanine hydroxylase (PAH) deficiency or tetrahydrobiopterin deficiency (BH4D) are not always available in low- or middle-income countries, including Mexico, limiting information regarding the phenotypic and genotypic characteristics of patients exhibiting BH4D. Objective. To report the genotypes underlying BH4D and the clinical presentation in unrelated Mexican HPA pediatric patients with normal PAH genotypes who attended a single metabolic reference center in Mexico. Methods. Automated Sanger sequencing of the PTS, QDPR, and PCBD1 genes of 14 HPA patients was performed. Predicted effects on protein structure caused by missense variants were assessed by in silico protein modeling. Results and discussion. A high prevalence of BH4D was noted in our HPA cohort (9.8%, N=14/142). Clinically relevant biallelic genotypes were identified in the PTS (N=7/14 patients), QDPR (N=6/14 patients), and PCBD1 (N=1/14 patients) genes. Four novel QDPR variants [c.714dup or p.(Leu239Thrfs*44), c.106-1G>T or p.(?), c.214G>T or p.(Gly72*), and c.187_189dup or p.(Gln63dup)] were identified. In silico protein modeling of six missense variants of PTS [p.(Thr67Met), p.(Glu81Ala), and p.(Tyr113Cys)], QDPR [p.(Cys161Phe) and p.(Pro172Leu)], and PCBD1 [p.(Glu97Lys)] supports their pathogenicity. Progressive neurological symptoms (mainly intellectual and motor impairment and even death in 4 patients) were noted in all patients with biallelic QDPR genotypes and in 5/7 patients bearing biallelic PTS genotypes. The single homozygous PCBD1 p.(Glu97Lys) patient remains asymptomatic. Conclusion. A higher proportion of BH4D (9.8 vs. 1-2% worldwide), attributable to a heterogeneous mutational spectrum and wide clinical presentation, was noted in our Mexican HPA cohort, with the PTS-related HPA disorder being the most frequent. Sequencing-based assays could be a reliable approach for diagnosing BH4D in our population.